Supramolecular structure using protein nanocages as the modular building blocks - Wijaya, Alvin Jonathan (2018)
In recent years, protein nanocages have been shown to be one the most promising and potential carriers in biomedicine industry. These highly symmetrical nanocage structures are formed and composed by the self-assembly mechanism of protein subunits in nanoscale size. These structures typically have three parts that are engineerable: the external, the internal and the inter-subunit. The exterior surface can be modified in such a way to increase its biocompatibility and targeting accuracy, while the interior surface is the part that can be loaded with diagnostic and/or therapeutic molecules. Lastly, the inter-subunit interactions have been shown to be responsible for the self-assembly modulation, in which the modifications of these interactions implicate directly to the molecular release mechanism. While it’s clear that these protein nanocages are very important and valuable for biomedicine, especially its applications for the drug delivery system, scientists have been constantly asking whether this caged structure can be stacked together to form a bigger molecular (supramolecular) structure.